The Role of Islamic Propagation Society International (IPSI) and Its Implementation of Interfaith Dialogue on Mosque Penang, Malaysia - Khalid, Muhammad Yusuf; Mazhisham, Panji Hidayat; Mohamad Hussain, Nur Husna; Mokhtar, Ahmad Najaa’; Mohd Noor, Khairunneezam; Mustafa, Muhamad Zaki (‘Abqari Journal, 2015)
This paper attempts to highlight the role of Islamic Propagation Society International (IPSI) in Interfaith Dialogue in Penang, Malaysia. Although the concept of interfaith dialogue is mentioned explicitly in the Holy Qur’an about 1400 years ago, it is still not commonly practiced today, partly because it needs the engagement from both sides, this regards for example the Muslim-Christian engagement. Due the wide spread of misconceptions and stereotypes against Islam in this era of globalization, Muslim scholars started to reactivate this divine effort. The contribution of late Ahmad Deedat who has inspired young Muslim to engage in this interfaith activity, as a result, the increasing number of Muslim personalities excel in this field such as Dr. Zakir Naik, Dr. Shabbir Ally, Hamza Tzortzis and Abdullah al-Andalusi to name a few. Surely, interfaith dialogue is one of the many effective ways to clear misconceptions about Islam and Muslims. This research is mainly based on observations and interviews at the Kapitan Keling mosque, Penang and IPSI headquarters in Penang. The research findings show that IPSI plays a very significant role in interfaith dialogue in Penang, and hence, the approach can be applied in any mosques in Malaysia which attracts many non-Muslim tourists such as Putra mosque and National mosque of Malaysia.